"It must have a substance in it": De blijvende betekenis van John Henry Newmans The Idea of a University: "It Must Have a Substance in it": The Enduring Significance of John Henry Newman’s The Idea of a University - Berkel, Klaas van (NTT, 2025)
In his valedictory lecture, Arie Molendijk in a friendly but compelling manner criticized the modern university as he had experienced it during the last 25 years. He however offered no alternative for a university that is dominated by consumerism, new public management and one-sided quality assessment. A renewed acquaintance with John Henry Newman’s The Idea of a University (1852) would have convinced him that this classical document on university education still offers inspiration for rethinking the university. Especially Newman’s remarks on knowledge being valuable as an end in itself and the persistence of this ideal throughout the ages would have provided him - and us - with a firm basis for a new vision of the university.